WP1: Innovations in partnerships, policies and platforms for the efficient, inclusive and climate resilient transformation of agrifood systems - Baum, Michael; Dhehibi, Boubaker; Akramov, Kamiljon; Najjar, Dina; Kurdi, Sikandra (International Center for Agricultural Research in the Dry Areas, 2022)
From Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA) WP1: Innovations in partnerships, policies and platforms for the efficient, inclusive and climate resilient transformation of agrifood systems Inception Workshop – Morocco May 17, 2022